Search for half-metallic ferrimagnetism in V-based heusler alloys Mn2VZ (Z = Al, Ga, In, Si, Ge, Sn) - Özdogan, K; Galanakis, I; Sasioglu, E; Atkas, B (Iop Publishing Ltd, 2006)
Using a state-of-the-art full-potential electronic structure method within the local spin density approximation, we study the electronic and magnetic structure of Mn2V-based full Hensler alloys: Mn(2)VZ (Z = Al, Ga, In, Si, Ge and Sn). We show that small expansion of the calculated theoretical equilibrium lattice constants restores the half-metallic ferrimagnetism in these compounds. Moreover, a small degree of disorder between the V and Z atoms, although it induces some states within the gap, preserves the Slater-Pauling behaviour of the spin magnetic moments and the alloys keep a high degree of spin polarization at the Fermi level, opening the way for a half-metallic compensated ferrimagnet.
Keywords: Magnetic-Properties